The combined effects of temperature and salinity on hatching success and survival of early life stages in the economically candidate marine mollusks : Spotted babylon Babylonia areolata - Nilnaj Chaitanawisuti; Nunim, Sirinun; Santhaweesuk, Wannanee (Journal of Research in Biology, 2011)
The combined effects of temperature and salinity on the hatching success and larval and juvenile survival of the spotted babylon Babylonia areolata were investigated in a 3x3 complete factorial experimental design employing three temperatures (25, 30 and 350C) and three salinities (27, 30 and 33‰). The results showed that hatching of egg capsules B. areolata was only significantly affected by salinity but not for temperature. No significant interaction between both factors occurred. However, survival of larvae and early juvenile were significantly affected by temperature and salinity. A significant interaction between both factors occurred in this experiment. The highest survival of early juveniles was founded at the lowest temperature (250C) with the highest salinity (33‰) and the highest temperature (250C) with the highest salinity (33‰). From an aquaculture point of view, high hatching of egg capsules B. areolata was obtained at temperature of 29 -350C and salinity above 32‰ to 33‰. As well as the high survival of larvae was obtained at temperature of 29 -30.50C and salinity above 32‰ to 33‰ and 29 -350C and 32 - 33‰ for early juveniles.